2003
DOI: 10.1200/jco.2003.06.080
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Primary Breast Sarcomas: A Series of Patients With Long-Term Follow-Up

Abstract: PBSs have the same clinical history and prognostic factors as sarcomas arising at other sites. Therefore, it is legitimate to use a similar treatment strategy for PBS as for other sarcomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
170
2
15

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(191 citation statements)
references
References 24 publications
4
170
2
15
Order By: Relevance
“…Tumour size seems to be the most frequently reliable prognostic factor in many of these series, as in breast carcinomas and softtissue sarcomas (Oberman, 1965;Norris and Taylor, 1968;Gutman et al, 1994;Barrow et al, 1999;Zelek et al, 2003) Other reported prognostic factors are the histopathological diagnosis (Barrow et al, 1999), the infiltrative features (Norris and Taylor, 1968;Barnes and Pietruszka, 1977), the histopathologic grading (Norris and Taylor, 1968;Barnes and Pietruszka, 1977;Gutman et al, 1994;Barrow et al, 1999;Zelek et al, 2003), presence of positive margins (Berg et al, 1962;Barrow et al, 1999), and extent of surgery for local recurrence (Pollard et al, 1990;North et al, 1998). Some authors found age to be of prognostic importance (Ludgate et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour size seems to be the most frequently reliable prognostic factor in many of these series, as in breast carcinomas and softtissue sarcomas (Oberman, 1965;Norris and Taylor, 1968;Gutman et al, 1994;Barrow et al, 1999;Zelek et al, 2003) Other reported prognostic factors are the histopathological diagnosis (Barrow et al, 1999), the infiltrative features (Norris and Taylor, 1968;Barnes and Pietruszka, 1977), the histopathologic grading (Norris and Taylor, 1968;Barnes and Pietruszka, 1977;Gutman et al, 1994;Barrow et al, 1999;Zelek et al, 2003), presence of positive margins (Berg et al, 1962;Barrow et al, 1999), and extent of surgery for local recurrence (Pollard et al, 1990;North et al, 1998). Some authors found age to be of prognostic importance (Ludgate et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…With small tumors, recurrence is usually local and distant metastases are infrequent. However, tumors larger than 5 cm are associated with distant metastases, independent of local recurrence [8].…”
Section: Discussionmentioning
confidence: 99%
“…However in present case the diagnosis could be made pre-operatively on NCB with help of IHC. Differential diagnosis of this rare tumor include: benign hemangioma, cystosarcoma phyllodes, stromal sarcoma, metaplastic carcinoma, fibrosarcoma, liposarcoma, squamous cell carcinoma with sarcomatoid features, myoepithelioma, fibromatosis, and reactive spindle cell proliferative lesion [2,8]. Surgical resection with mastectomy is the usual treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, PTs range from benign to malignant lesions. The ductal component is usually benign, whereas malignancy develops in the mesenchymal portion of phyllodes tumour, which can contain liposarcomatous, leiomyosarcomatous, chondrosarcomatous, osteosarcomatous and/or angiosarcomatous constituents, singly or variably admixed [3,4]. Malignant PT most commonly metastasizes to the lungs and to the bones [4].…”
Section: Introductionmentioning
confidence: 99%